Associations between access to alcohol outlets and alcohol intake and depressive symptoms in women from socioeconomically disadvantaged neighbourhoods in Australia. (December 2017) - Lamb, Karen; Thornton, Lukar; Teychenne, Megan; Milte, Catherine; Cerin, Ester; Ball, Kylie
Abstract Background This study examined associations between alcohol outlet access and alcohol intake, depressive symptoms score and risk of depression among women residing in disadvantaged neighbourhoods in Victoria, Australia. Methods Data on depressive symptoms, alcohol intake and socio-demographic characteristics were obtained from a sample of 995 adult women from Victoria, Australia who were surveyed as part of the Resilience in Eating and Activity Despite Inequality (READI) study. The location of all licensed alcohol outlets in Victoria was obtained from the Victorian Commission for Gambling and Liquor Regulation. Participant and alcohol outlet addresses were geocoded to calculate individual alcohol outlet access, defined as the number of outlets (all and by sub-type) within 0.4 km and 3 km of participants' homes. Separate regression models with clustered standard errors were fitted to examine associations between access and alcohol intake according to national recommended limits for short- and long-term harm, frequency of consumption above long-term harm guidelines, depressive symptoms score and risk of depression. Results Odds of consumption within short-term harm guidelines (≤4 drinks on any day) decreased with increasing access within 3 km, irrespective of outlet type. Typically, there was no evidence to support associations between access and consumption above long-term harm guidelines (>2 drinks on any day) unless considering frequency of consumption at this level where results showed decreased odds of 'don't drink' versus frequently drinking above long-term harm guidelines (i.e., >2 drinks at least once per week) with increasing access at either distance. Although there was no evidence of an association between any of the alcohol outlet access measures and depressive symptoms score, odds of being at risk of depression decreased with increasing access within 3 km. Conclusions This study found some evidence to support an association between increasing alcohol outlet densities of all types and harmful levels of alcohol consumption, and the association appears to be dependent on the distance threshold considered, among women residing in socioeconomically disadvantaged neighbourhoods within Victoria, Australia. However, higher numbers of alcohol outlets appear to be associated with a slightly lower risk of depression, with further research needed to identify the direction and mechanisms underlying this unintuitive association.